2009
DOI: 10.1016/j.talanta.2009.06.053
|View full text |Cite
|
Sign up to set email alerts
|

Determination of organic and inorganic mercury species in water and sediment samples by HPLC on-line coupled with ICP-MS

Abstract: This paper describes a preconcentration method for Hg(2+) and MeHg(+) in water samples using sodium diethyldithiocarbamate immobilized in polyurethane foam (PU-NaDDC) and an extraction method for several mercury species in sediment samples, including MeHg(+), EtHg(+) and PhHg(+), which is simple, rapid, and uses a single organic solvent. Separation and measurement were done by high-performance liquid chromatography on-line with inductively coupled plasma mass spectrometry (HPLC/ICP-MS). Initially, the test of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(43 citation statements)
references
References 26 publications
1
40
0
2
Order By: Relevance
“…이러한 문제점 때문에 최근 선진국에서는 전처리가 단순하 며 정량 시 방해물질의 영향을 받지 않는 액체크로마토그래피 를 이용하여 메틸수은을 분리 한 후 유도결합플라즈마/질량분 석기로 part per billion까지 정량하는 방법들의 연구가 진행 중에 있으나, 우리나라에서는 아직 어류 중에서 메틸수은 분석 에 HPLC-ICP/MS를 이용한 연구가 미비한 실정이다 (Qvarnstrőm et al, 2002;Santos et al, 2009 (Fig. 1).…”
Section: 어류 중 다랑어류 새치류 및 심해성 어류는 총수은의unclassified
“…이러한 문제점 때문에 최근 선진국에서는 전처리가 단순하 며 정량 시 방해물질의 영향을 받지 않는 액체크로마토그래피 를 이용하여 메틸수은을 분리 한 후 유도결합플라즈마/질량분 석기로 part per billion까지 정량하는 방법들의 연구가 진행 중에 있으나, 우리나라에서는 아직 어류 중에서 메틸수은 분석 에 HPLC-ICP/MS를 이용한 연구가 미비한 실정이다 (Qvarnstrőm et al, 2002;Santos et al, 2009 (Fig. 1).…”
Section: 어류 중 다랑어류 새치류 및 심해성 어류는 총수은의unclassified
“…94 Kehrig et al 95 determined methylmercury (MeHg) and total Hg in water and fish samples from two reservoirs within Brazilian Amazon and observed that the bioconcentration factor (BCF) is higher in ecosystem rich in dissolved organic matter. Santos et al 96 coupled HPLC and ICP-MS for determination of organic and inorganic Hg species in water samples. The authors used sodium diethyldithiocarbamate immobilized in polyurethane foam to preconcentrate Hg(II) and MeHg(I).…”
Section: Environmentalmentioning
confidence: 99%
“…For example, HPLC or GC or CE hyphenated with atomic fluorescence spectrometry (AFS) or inductively coupled plasma mass spectrometry (ICP-MS) [4][5][6][7][8][9][10][11][12][13][14][15][16]. Among all above hyphenated techniques, CE-ICP-MS has attracted increasing attention since CE has higher separation efficiency for all ionic and neutral species, tiny sample requirement, various separation modes and low operating cost [17][18][19], and ICP-MS has short detection time, broad dynamic range, multi-element capabilities, excellent mass resolution and high sensitivity for almost metallic ions.…”
Section: Introductionmentioning
confidence: 99%